Syndemic of Lifetime Mental Illness, Substance Use Disorders, and Trauma and Their Association With Adverse Perinatal Outcomes. Issue 1 (January 2020) - McDonald, Lynn R.; Antoine, Denis G.; Liao, Caiyun; Lee, Amy; Wahab, Maybel; Coleman, Jenell S.
Adverse perinatal outcomes are a significant contributor to neonatal and infant deaths. Mental illness, substance use disorders, and interpersonal trauma are often prevalent within obstetrical populations. Previous literature has documented the individual associations between these psychosocial factors and adverse perinatal outcomes. The co-occurrence of these three psychosocial factors might represent a syndemic among pregnant women, although they have not been described as such in the literature. Analysis of the interrelatedness and aggregate effect of these factors may allow for a more effective screening process that may reduce adverse perinatal outcomes. The objective of this article is to examine whether psychosocial factors (mental illness, substance use disorders, and interpersonal trauma) were independently and synergistically associated with adverse perinatal outcomes. This is a retrospective cohort study of 1, 656 pregnant women at a single institution. Perinatal outcome and psychosocial data were abstracted from each participant's electronic medical record. Univariate and bivariate analyses, and multiple logistic regression were performed. Mean age was 27.5 ( SD = 6.2) years. The majority was Black (60.6%) and single (58%). Psychosocial factors were reported in 35% of women. The incidence of adverse perinatal outcomes increased with greater number of psychosocial factors: 21.2% if no psychosocial factor, 27.0% if one psychosocial factor, 27.4% if two, and 35.3% if all three (for trend, p = .01). Women who reported all three psychosocial factors had twice the odds of adverse perinatal outcomes (adjusted odds ratio = 2.04, 95% confidence interval = [1.09, 3.81], p = .03) compared with those who reported none. Our data suggest there is a synergistic relationship between the psychosocial factors that is associated with increased adverse perinatal outcomes. A validated screening tool is needed to stratify patient's risk of adverse perinatal outcomes based on psychosocial factors. Such screening could lead to tailored interventions that could decrease adverse perinatal outcomes.